2017
DOI: 10.1371/journal.pone.0169126
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Investigate Single-Strand DNA Responses in G1 Human Cells via a Telomere-Targeted, Nuclease-Deficient CRISPR-Cas9 System

Abstract: DNA replication stress has the potential to compromise genomic stability and, therefore, cells have developed elaborate mechanisms to detect and resolve problems that may arise during DNA replication. The presence of single-stranded DNA (ssDNA) is often associated with DNA replication stress and serves as a signal for both checkpoint and repair responses. In this study, we exploited a CRISPR-Cas9 system to induce regions of ssDNA in the genome. Specifically, single-guide RNAs bearing sequence complementarity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Localization of nuclease-deficient Cas9 to telomeres with a single-guide RNA complementary to telomeric repeat DNA leads to the formation of RNA–DNA duplexes that leave one telomeric DNA single-stranded and capable of recruiting RPA and other factors involved in DDR. This model can be used to study RPA recruitment in G1 cells and has potential for application on other genomic repeats ( 363 ).…”
Section: New Tools To Study Rpa Dynamics On Dna and Their Applications In Diagnosticsmentioning
confidence: 99%
“…Localization of nuclease-deficient Cas9 to telomeres with a single-guide RNA complementary to telomeric repeat DNA leads to the formation of RNA–DNA duplexes that leave one telomeric DNA single-stranded and capable of recruiting RPA and other factors involved in DDR. This model can be used to study RPA recruitment in G1 cells and has potential for application on other genomic repeats ( 363 ).…”
Section: New Tools To Study Rpa Dynamics On Dna and Their Applications In Diagnosticsmentioning
confidence: 99%
“…2F ). Furthermore, several recent reports have demonstrated functions for Rad51 in G0/G1 phase in either the repair of artificially generated DNA damage at specific genomic regions site-specific DSBs (Crefcoeur et al, 2017; Wei et al, 2015; Yilmaz et al, 2021) or under conditions that allow for DNA end resection (Chen et al, 2021; Orthwein et al, 2015; Xie et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the disruption of proteins and other factors that regulate the expression or stability of HR proteins have both been shown to promote end resection and Rad51 foci formation in G0/G1 (Chen et al, 2021; Orthwein et al, 2015; Xie et al, 2020). Furthermore, studies that have generated DSBs at centromeric regions (Yilmaz et al, 2021) and recruited Cas9 to telomeric DNA to induce ssDNA (Crefcoeur et al, 2017) have shown that Rad51 can be recruited to these specific chromosomal regions characterized by repetitive DNA elements. Finally, the site-specific induction of oxidative stress at a define genomic locus was shown to lead to the recruitment of Rad51 and other HR factors in a transcription- and CSB-dependent manner (Wei et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation